2018
DOI: 10.1007/s11255-017-1778-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic usefulness of soluble urokinase plasminogen activator receptor in hemodialysis patients

Abstract: PurposeConsidering its prognostic usefulness and the relationship with chronic kidney disease, we analyzed the clinical utility of soluble urokinase plasminogen activator receptor (suPAR) in end-stage renal disease patients undergoing hemodialysis treatment. We focused on the association between suPAR levels and clinical outcomes, especially those related to cardiovascular events and mortality as well as the effect of hemodialysis on the protein levels.MethodsWe enrolled 64 patients. Blood samples for laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
3
14
1
Order By: Relevance
“…The present study excluded patients with CKD at stages greater than 3a. Nevertheless, suPAR level was found to strongly correlate with creatinine concentration and GFR across the studied group, which is in accordance with previous studies 2 4 , 18 , 19 . We are aware that the CKD-EPI formula was not standardized for the population of seniors 13 ; however, we used this formula, as currently recommended, to remain comparability with other studies concerning suPAR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study excluded patients with CKD at stages greater than 3a. Nevertheless, suPAR level was found to strongly correlate with creatinine concentration and GFR across the studied group, which is in accordance with previous studies 2 4 , 18 , 19 . We are aware that the CKD-EPI formula was not standardized for the population of seniors 13 ; however, we used this formula, as currently recommended, to remain comparability with other studies concerning suPAR.…”
Section: Discussionsupporting
confidence: 92%
“…suPAR level was also found to strongly correlate with laboratory markers of kidney function. This observation is in accordance with the observation that in chronic kidney disease (CKD) the biomarker correlates with reduced GFR 18 , 19 . The present study excluded patients with CKD at stages greater than 3a.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the pathogenesis of pFSGS, circulating factors have been regarded as significant because in about 40% of patients, this disease recurs after transplantation [2, 3]. The soluble urokinase plasminogen activator receptor (suPAR) is a protein circulating in the human blood and body fluids, which is present at low concentration in healthy individuals and high levels in patients with infections, chronic kidney disease (CKD), and other inflammatory disorders [4]. In that, its usefulness as a biomarker has been investigated in various diseases, such as sepsis [5], pneumonia [6], chronic obstructive pulmonary disease (COPD) [7], and kidney diseases including pFSGS [3, 810].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that suPAR is associated with the coronary artery calcification (CAC) score (CACS) independently of the systematic coronary risk, and provides prognostic information on the CVD risk in the general population [4-7]. suPAR is also a biomarker strongly predictive of cardiovascular outcome in the pathogenesis of diabetic renal disease patients treated with hemodialysis [8-9]. However, it is unclear whether suPAR levels are associated with CAC in patients undergoing hemodialysis.…”
Section: Introductionmentioning
confidence: 99%